Cyclic performance of circular concrete-filled steel tubular members with initial gap between tube and concrete core. Issue 1 (January 2020) - Liao, Fei-Yu; Zhang, Wei-Jie; Han, Hao
It is common that initial gaps exist between the steel tube and the core concrete in concrete-filled steel tubular structural members, which might affect the performance of the structure. This article aims to study the effects of the gaps on the cyclic behaviour of circular concrete-filled steel tubular members. A total of 24 concrete-filled steel tubular specimens were tested under constant axial load and cyclically lateral loads, where the main testing parameters included the types of gap, the gap ratio, the axial load level and the steel ratio. The failure mode, lateral load versus lateral displacement hysteretic curve and load versus displacement envelope curve of concrete-filled steel tubular specimens with pre-designed gaps were experimentally investigated and compared with those of the reference ones without any gap. The effects of gaps on the ultimate strength, ductility and dissipated energy of the concrete-filled steel tubular members were quantitatively evaluated according to the test results. The influence of gaps on circular concrete-filled steel tubes under different loading conditions, such as axial compressive loading, pure bending, eccentrically compressive loading and cyclic lateral loading, was also compared and discussed.